Asymetrie analysis of the arm segments during forward handspring on floor - Exell, T.; Irwin, G.; Godden, S.; Kerwin, D. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The aim of this study was to examine kinematic and kinetic asymmetries of the arm segments during the contact phase of the forward handspring on floor. Four female National level gymnasts (19 y, 58.64 kg, 1.62 m) performed 15 forward handsprings whilst synchronised 3D kinematic and kinetic data were collected. Percentage differences in symmetry angles between the left and right arms were quantified. Significant kinetic asymmetry was observed for all gymnasts (p<0.05) with the direction of the asymmetry being related to the lead leg. Kinematic asymmetry was present at the shoulder, but not at the distal segments. These findings provide useful information for coaching gymnastics skills, which may subjectively appear to be symmetrical.